Prolegomena zu einer Wissenschaftlichen Mythologie - Müller, Carl Otfried (Cambridge library collection. Classics, 1825)
This pioneering work by the influential German classicist Karl Ottfried Müller (1797–1840) was one of the earliest scholarly books to address the question of the origins and meaning of the Greek myths. Published in Göttingen in 1825, it proposes a definition of 'myth' and goes on to suggest how possible sources for myths might be identified in historical events. Müller discusses how the age of particular myths might be established, either from the dates of such events, or from datable references to the myths in literary sources, and how the original substance of a myth might be distinguished from later accretions or modifications in poetry and prose. He also considers the interpretation of myths and their symbolic functions. Müller concludes with examples of how his method might be applied to particular cases, and a chapter comparing his proposals with those of other scholars